2012
DOI: 10.1371/journal.pone.0048494
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of the Hfq-Regulon in Sinorhizobium meliloti 2011

Abstract: Riboregulation stands for RNA-based control of gene expression. In bacteria, small non-coding RNAs (sRNAs) are a major class of riboregulatory elements, most of which act at the post-transcriptional level by base-pairing target mRNA genes. The RNA chaperone Hfq facilitates antisense interactions between target mRNAs and regulatory sRNAs, thus influencing mRNA stability and/or translation rate. In the α-proteobacterium Sinorhizobium meliloti strain 2011, the identification and detection of multiple sRNAs genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 79 publications
2
41
0
Order By: Relevance
“…28,29,31,32 Despite of relevant differences in the experimental setups (i.e., biological conditions tested) preclude direct comparison of the mRNAs of the Hfq regulon and those scored as Hfq-associated in our study, an overlap of 322 genes was found between both data sets ( Table S3). Almost half of these genes (158) encode transport proteins (mostly ABC transporter membrane complexes), cytoplasmic metabolic enzymes such as the phosphoenolpyruvate carboxykinase (PckA; Fig.…”
Section: Hfq-dependent Mrnasmentioning
confidence: 95%
See 2 more Smart Citations
“…28,29,31,32 Despite of relevant differences in the experimental setups (i.e., biological conditions tested) preclude direct comparison of the mRNAs of the Hfq regulon and those scored as Hfq-associated in our study, an overlap of 322 genes was found between both data sets ( Table S3). Almost half of these genes (158) encode transport proteins (mostly ABC transporter membrane complexes), cytoplasmic metabolic enzymes such as the phosphoenolpyruvate carboxykinase (PckA; Fig.…”
Section: Hfq-dependent Mrnasmentioning
confidence: 95%
“…Remarkably, the S. meliloti hfq mutants evidenced massive misregulation of transport systems, which anticipates a major role of Hfq in controlling the metabolic versatility of this bacterium. 28,29,31,32 Not unexpectedly, this global influence of Hfq on S. meliloti physiology was also found to compromise an array of symbiotic traits, including competitiveness for Northern analysis of the expression of selected hfq-bound sRNas. Total RNa was obtained from strain sm2B3001 grown in the conditions of coIP experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment of the cell harvesting, aliquots of cultures containing 40 OD units each were mixed with their respective pair for proteomic comparison and cooled on ice before centrifuging to collect cell pellets. Proteins were extracted and separated into the cytosolic and membrane subcellular fractions following the protocol described elsewhere (24). The protein concentration in each fraction was determined by the Bradford colorimetric assay (Bradford protein assay Ready-to-Use; Bio-Rad, USA) (65) with a bovine serum albumin solution as a reference, and the quality was verified by SDS-PAGE (62).…”
Section: Methodsmentioning
confidence: 99%
“…meliloti has been shown to express more than 400 different sRNAs under different growth conditions and lifestyles, i.e., both free-living in the soil and symbiotically associated in a plant (15)(16)(17)(18)(19)(20)(21). In addition, S. meliloti expresses a functional homolog of the Escherichia coli Hfq protein, a chaperone of RNA-RNA interactions and a modulator of RNA activity (22)(23)(24)(25)(26)(27)(28)(29). Nevertheless, the biological implications of the large S. meliloti RNome remain largely unexplored (20), since only four small RNAs have been functionally characterized so far, i.e., the cell cycle regulator sRNA EcpR1 (30), the quorumsensing regulator sRNA RcsR1 (31), and the tandemly encoded orthologs AbcR1 and AbcR2 (32).…”
mentioning
confidence: 99%